TRAINING IN CONFLICT MANAGEMENT SKILLS FORMATION OF PROSPECTIVE EXPERTS ON MERCHANDISING AND COMMERCE - Korostelin, Mykhailo O. (Educological discourse, 2015)
The article explores the essence of the «training» phenomenon, its principal elements, internal methods (group discussion, exercises and role-play games); the focus was the leading principles of trainings conduction. The viability of employment of training aiming to develop conflict management skills of prospective experts on merchandising and commerce was substantiated. The essence of interconnected content units was explored – personal, communicative, professional. The main training procedures were emphasized among which definition and evaluation of challenging conflict situations requiring simulation, instruction and reinforcement were differentiated. The necessity of the balanced amalgamation of organizational communicational forms during the training was outlined: individual-group communicating, in-pairs communicating, small groups communicating. The essence of original trainings was explored: «Industrial disputes», «Team work efficiency», «Intrapersonal conflicts prevention». In the course of the training its efficiency was stated which gave the ground to claim the viability of its application aiming to develop conflict management skills.